Masculinity and Femininity in Question - Pauline Herlambang; Jenny M. Djundjung (Institute of Research and Community Outreach - Petra Christian University, 2015)
The character traits in Shinchan seem to be contrary to the structure of masculine and feminine traits. I am interested in discussing the feminine character traits that are adopted by the male characters and the masculine character traits that are adopted by the female characters in a patriarchal society in Japan. Under the patriarchal system, there are rigid segregation of gender roles and the expected feminine and masculine traits. The main purpose of this paper is that even though some of the male characters adopt the feminine character traits and the female characters adopt the masculine character traits, the gender roles Japanese patriarchal system remains unchanged